Quality assessment methodology for sign language mobile apps using fusion of enhanced weighted mobile app rating scale (MARS) and content expert standardized criteria - Dianes David Emmanuel (Tanjong Malim, 2023)
Quality assessment methodology for sign language mobile apps using fusion of enhanced weighted mobile app rating scale (MARS) and content expert standardized criteria by Dianes David Emmanuel